Public sentiment and explicit ethical expression in social media discourse on brain–computer interfaces: an observational analysis. - Xie, Xiangdong; Luo, Huiyu (Humanities & Social Sciences Communications, 2026)
Brain–computer interfaces (BCIs) are rapidly moving toward clinical translation and commercial deployment, even as their growing public visibility continues to generate ethical controversy. Yet existing research has rarely examined, in an integrated manner, the overall sentiment dynamics of BCI-related discourse on social media, the prevalence and internal structure of explicit ethical expression, and short-term fluctuations surrounding major real-world events. We conducted an observational analysis of public posts on X (formerly Twitter) from January 1, 2019, to December 31, 2024. The initial dataset comprised 23,240 posts; after preprocessing and eligibility screening, 16,632 posts were retained for the main analysis. Sentiment was assessed using VADER, and a custom ethics lexicon was applied to identify explicit ethical expression, yielding an ethics-related subcorpus of 1488 posts (8.95%). We then examined the distribution of ethical domains, performed event-window analyses comparing the three months before and after key events, and conducted double-coding validation and duplicate-free robustness checks. Positive, neutral, and negative posts accounted for 48.69%, 38.23%, and 13.08% of the analytic corpus, respectively, and Mann–Kendall trend tests indicated that overall sentiment became more positive over time (compound mean: S = 648, Z = 3.145, P = 0.002; positive posts: S = 1069, Z = 5.192, P < 0.001). Within the ethics-related subcorpus, safety and risk (64.65%) emerged as the most salient ethical domain, followed by governance and accountability (12.50%) and privacy and neurorights (12.16%). Event-window analyses further showed that technological breakthroughs and regulatory advances were generally associated with more positive short-term shifts, whereas controversial events were more likely to coincide with increased negative expression. Taken together, these findings suggest that BCI-related discourse on social media has become increasingly positive overall, but that this positivity has not displaced ethical contestation. Instead, normative concerns surrounding risk, safety, governance, and privacy persist alongside technological optimism. Public acceptance of BCIs should therefore be understood not as a static position of support or opposition, but as a dynamic process continuously reshaped by technological developments, ethical controversy, and platform-mediated communication.